MEDICAL ETHICS: AYURVEDIC VIEW POINT IN PURVIEW OF CHARAK SAMHITA - Sharma, Dr Nidhi (Journal of Biomedical and Pharmaceutical Research, 2018)
Ethics are the methods, policies, perspectives which decide a set of guidelines to act in a particular situation and for analyzing complex problem courses. The medical profession is governed by legislation and by code of ethics and etiquette. The ethical code in medicine has found their place from the very beginning. Ayurveda is the most ancient medical science. Charak Samhita is the one of the ancient authentic treatise of Ayurveda medicine. The code of ethics has been described on various places in the aforesaid text. The significance of ethical codes have increases manifold with the advent of time considering the shift of focus from serving mankind to financial benefits. The present paper deals with the review of medical ethics in Charak Samhita and analysis of their contemporary relevance. Key words: Ayurveda, Ethics, Charak Samhita